Application of Multiple Ultrasonic Techniques in the Diagnosis of Prostate Cancer - Liu, Yushan; Zeng, Shi; Xu, Ran (Frontiers in Oncology, 2022)
Methods for diagnosing prostate cancer (PCa) are developing in the direction of imaging. Advanced ultrasound examination modes include micro-Doppler, computerized-transrectal ultrasound, elastography, contrast-enhanced ultrasound and microultrasound. When two or more of these modes are used in PCa diagnosis, the combined technique is called multiparameter ultrasound (mp-US). Mp-US provides complementary information to multiparameter magnetic resonance imaging (mp-MRI) for diagnosing PCa. At present, no study has attempted to combine the characteristics of different ultrasound modes with advanced classification systems similar to the PIRADS system in mpMRI for the diagnosis of PCa. As an imaging method, mp-US has great potential in the diagnosis of PCa.